1997
DOI: 10.1073/pnas.94.17.9040
|View full text |Cite
|
Sign up to set email alerts
|

A thyroid hormone receptor coactivator negatively regulated by the retinoblastoma protein

Abstract: The retinoblastoma protein (Rb) plays a critical role in cell proliferation, differentiation, and development. To decipher the mechanism of Rb function at the molecular level, we have systematically characterized a number of Rb-interacting proteins, among which is the clone C5 described here, which encodes a protein of 1,978 amino acids with an estimated molecular mass of 230 kDa. The corresponding gene was assigned to chromosome 14q31, the same region where genetic alterations have been associated with severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 50 publications
3
58
0
Order By: Relevance
“…Taken together, these data argue against a role of Rb phosphorylation in transcriptional enhancement. Similarly, the Rb/Sp1, Rb/Trip230, and Rb/Cbfa1 interactions were also shown to be independent of Rb phosphorylation (12,24,37). These results suggest a mechanism by which Rb, irrespective of its phosphorylation status, may be recruited to promoter sequences and play a significant role in transcriptional regulatory processes.…”
Section: Rb Function In Activation Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these data argue against a role of Rb phosphorylation in transcriptional enhancement. Similarly, the Rb/Sp1, Rb/Trip230, and Rb/Cbfa1 interactions were also shown to be independent of Rb phosphorylation (12,24,37). These results suggest a mechanism by which Rb, irrespective of its phosphorylation status, may be recruited to promoter sequences and play a significant role in transcriptional regulatory processes.…”
Section: Rb Function In Activation Andmentioning
confidence: 99%
“…Indeed Rb enhances the activity of GR through interaction with the Brm/ BRG1 sub-units of the SWI/SNF complex (10) and the activity of the androgen receptor independently of BRG1 (11). Rb also regulates negatively the activity of the thyroid hormone receptor by interacting with and inhibiting the coactivator Trip230 (12) and inhibits PPAR␥-dependent transcription (13). Rb can also interact with the RIZ protein, which in turn interacts with the estrogen receptor (ER) in a ligand-dependent manner (14).…”
mentioning
confidence: 99%
“…In addition, it was demonstrated that Rb negatively regulated the TRIP230 coactivation function of TRregulated transcription. 232 The manner in which Rb facilitates repression is less clear, although it may involve sequestration of TRIP230. 232 However, this does illustrate a salient point, which is that transcription is tightly regulated at many levels.…”
Section: Transcriptional Coactivation Of the Ahrcmentioning
confidence: 99%
“…The ability of pRb to modulate HIF-1 transcriptional activity is borne out by studies on the thyroid hormone receptor/RB-interacting protein 230 (TRIP230), a transcription coactivator that is negatively regulated by pRb binding (Chang et al, 1997). Under hypoxic conditions, TRIP230 is recruited by HIF-1b/ARNT on HRE sequences and it is indispensable as a transcription coactivator for HIF-1-regulated genes, in particular the VEGF gene (Beischlag et al, 2004).…”
Section: Modulation Of Angiogenesis-related Transcription Factors By Prbmentioning
confidence: 99%